Inorganic 3D Structures - Vegas, Angel (Structure and Bonding, 2011)
D. Santamaría-Pérez and F. Liebau : Structural relationships between intermetallic clathrates, porous tectosilicates and clathrates hydrates Vladislav A. Blatov: Crystal structures of inorganic oxoacid salts perceived as cation arrays: a periodic graph approach Ángel Vegas: FeLiPO4: Dissection of a crystal structure. The parts and the whole D. J. M. Bevan, R. L. Martin, Ángel Vegas: Rationalisation of the substructures derived from the three fluorite-related [Li6(MVLi)N4] polymorphs: An analysis in terms of the "Bärnighausen Trees" and of the "Extended Zintl-Klemm Concept" Ángel Vegas: Concurrent pathways in the phase transitions of alloys and oxides: Towards an Unified Vision of Inorganic Solids  .